Javelin Throwing Technique: A Biomechanical Study - Hussain, I.; Bari, M. A. (Computer Engineering and Intelligent Systems, 2012)
The purpose of this study was to analyze by correlational methods the biomechanical factors involved in achieving the maximal distance thrown in the javelin event. Six athlete from Aligarh Muslim University, Aligarh India were filmed by a two high speed Canon Legaria SF-10, 8.1 Mp cameras in a field setting with (1/2000 shutter speed and at 30-60fps). The cameras were set-up on a rigid tripod and secured to the floor in the location. First camera was located to obtain maximum accuracy and second camera located to view the throwing performances, at given specified distance in the reconstruction of the two dimensional co-ordinate. The locations of camera were chosen so that the optical axes of camera intersected perpendicularly to the designated plane. Results of this study shows positive significant correlation was found between the throwing distance and the initial velocity, insignificant correlations were found between the throw distance and the release angle, attitude angle, attack angle and release height of javelin at the moment of javelin release. The results suggest that in order to attain maximal distance thrown the javelin thrower should achieve positive acceleration during the running approach, effective thrusting with the right leg on the penultimate stride and carry the javelin during the last strides at the optimal angle of release.